Perspectives on Music Pedagogy in Informal, Performance-Based Learning - Riyan Hidayatullah (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2023)
Music learning practices in formal settings, for example, in the classroom, generally apply structured and systematic curriculum-based learning strategies. The entire learning process has generally been organized and implemented with guidance and supervision by the teacher. In Indonesia, music learning in formal schools still applies the standardization of Western music theory. In fact, music learning practices that offer local pedagogical values provide a very diverse portrait. In higher education, music learning that applies local pedagogy has been going on for some time. The Music Education Study Program (PSPM) of Lampung University is one of the tertiary educational institutions that has implemented music learning practices based on local pedagogy. Learning practices that are also performance-based are carried out with "informal" stages and processes. This notion means that local pedagogy is based on informal music practices in Lampung society. Informal music learning practices have not been recognized as the curriculum of formal institutions. This article looks at the concept of Lampung local pedagogy applied in music performance-based learning practices in formal areas. The central theoretical perspective in this research uses Green's (2008) thoughts on informal learning in the classroom. Data were collected through observation and in-depth interviews with lecturers and students of levels 2 and 3. As a result, the concept of local music pedagogy that takes place in music performance-based learning at PSPM University of Lampung (1) provides opportunities for students to learn while creating; (2) provides space for collaboration and social participation; and (3) strengthens peer learning in groups.